Poca adherencia al tratamiento farmacológico en pacientes hipertensos que acuden al hospital del IESS en Esmeraldas - Páez-Landeta, Rubén (2016)
Context: it is usual to identify reduced adherence to the pharmacological treatment of arterial hypertension, which increases mortality due mainly to chronic non-communicable diseases. Objective: to determine adherence to drug treatment in hypertensive patients, treated at the General Hospital of the Ecuadorian Social Security Institute of Esmeraldas. Methods: an observational, descriptive and cross-sectional study was conducted on patients interviewed in an outpatient clinic using the Morisky-Green Test, to assess adherence to antihypertensive drug treatment. Results: 247 patients were studied, 58.7% men with a disease time from May to 3 years (61.3%). Adherence to pharmacological treatment was 47.4%, with greater adherence being observed in individuals with a marital status and higher education (p <0.05). Conclusion: adherence to drug treatment in hypertensive patients is less than 50% and it is positively related to the degree of education.